Vancomycin-hybrid bimetallic Au/Ag composite nanoparticles: preparation of the nanoparticles and characterization of the antibacterial activity. (14th June 2017) - Lu, Zhentan; Zhang, Jiaqi; Yu, Zhenguo; Liu, Xing; Zhang, Zhifeng; Wang, Wenwen; Wang, Xiaojun; Wang, Yuedan; Wang, Dong
Abstract : The Bimetallic Au/Ag composite nanoparticles have enhanced antibacterial activity and weak bacterial resistance. Abstract : We report vancomycin-hybrid bimetallic nanoparticles (Au/AgNPs@Van) that can adhere to bacterial surfaces with high antibacterial activity. The Ag/AuNPs@Van also show weaker bacterial drug resistance than free vancomycin, and have a low cytotoxicity. Ag/AuNPs@Van has a promising future in the treatment of infectious diseases.